Economic losses from US hurricanes consistent with an influence from climate change - Estrada, Francisco; Botzen, W. J. Wouter; Tol, Richard S.J. (Nature Geoscience, 2015)
The observed increases in hurricane losses are often thought to result solely from societal change. A regression-based analysis of US economic losses reveals an upward trend between 1900 and 2005 that is not explained by increasing vulnerability.